OFFENSES AGAINST THE ENVIRONMENT, ESSENTIAL DAMAGE ASSESSMENT IN THEORY AND PRACTICE - Kotāne, Silvija (Administrative and Criminal Justice, 2017)
This paper shall review of the development of environmental criminal – legal protection in the Republic of Latvia. One of the most complicated valuation terms in Criminal law is essential harm. The adverse effects of marking, used assessment concept – "essential harm" to the Criminal Law Section 11, provisions are included as a criminal offense frame sign. Valuation concept „essential harm” or “significant damage” is widely used. Material injury is one of the mandatory features of the objective of acriminal offence defining the legal classification of the offence and, inany particular case, to assess the nature and consequences of thedamage in relation to the interests laid down by the law. In all cases, regulation is not specified. Significant damage and other interests protected by law in nature and severity to determine the natural environment, human health can be an expert evaluation. In deciding the question of material injury, which is especially qualifying characteristic of the Criminal Law Article 109, followed to the Special Law Annex 1 "Criteria for the detectable threat or significant risk to the law protected the interests of the forest environment conservation." With regard to essential harm the forest environment, evaluation is embedded in the law and are applied in practice.